Comparative Study of Ni-W/CeO25 Ni-W/y-Al2O3 and Ni-WIHT CataIysts for H2 Production by Steam Reforming of Bioethanol - Hernández, Paz; Fernández, Arturo; Messina, Sarah (2011)
Ni-W cataIysts supportedon Ce02.~03andhydrota1cite (HT)were studiedin th.e steamreformingofethanol at 500-650DC. The Ce02 and HT were synthesized by impregnation and direct coprecipitation methods, respectively. Commercia1~03 was used. Nicke} content was varied from !O, 15 and 30% with 1 % W. The catalyst that presentod the highest cataIytic activity and selectivity to bydrogen was 10% Ni-WIHT. Conversian to eth.anol was 100% and selectivities to H2 CH4 CO2 and ca were 75, 5.78, 0.37 and 18.85%, respectively, at a temperature of 500ºC. Moreover, these catalysts showed good stability with respect to carbon deposition and low selectivity towards ~~ production. These are desirablc features for cataIysts to be used in hydrogen production for fuel cell applications.